2011
DOI: 10.4103/0300-1652.93799
|View full text |Cite
|
Sign up to set email alerts
|

Does concern about halitosis influence individual′s oral hygiene practices?

Abstract: Objective:The objective of this study was to assess whether the concern about halitosis influence oral health attitude and practices among young literate adults in Nigeria.Materials and Methods:This cross-sectional survey of 400 randomly selected temporary camp resident adults in Anambra state, South Eastern Nigeria was conducted using a modified version of the Hiroshima University-Dental Behavioral Inventory questionnaire.Results:Out of the 400 questionnaires distributed, only 294 were filled and returned giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…In this study, the proportion of respondents who concerned halitosis was so high (91.8%). A study on halitosis concern on Nigeria reported that more than half of the participants expressed concern about halitosis [15]. And also, results from the current study is higher than the study among the high schools' male students in Tokyo with 55.4%, 40% in Brazil high school students, 66.3% in among Indian dental students and 78% in Jordanian population [2,[17][18][19].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…In this study, the proportion of respondents who concerned halitosis was so high (91.8%). A study on halitosis concern on Nigeria reported that more than half of the participants expressed concern about halitosis [15]. And also, results from the current study is higher than the study among the high schools' male students in Tokyo with 55.4%, 40% in Brazil high school students, 66.3% in among Indian dental students and 78% in Jordanian population [2,[17][18][19].…”
Section: Discussionmentioning
confidence: 52%
“…A self-completed questionnaire collected socio-demographic information (such as age, gender, and education level), the experience of health education, self-perceived oral health status, knowledge of oral health (7 questions) and an individual's halitosis concern "Do you worry about having oral bad breath". Questions on oral health knowledge and behaviors were collected based on Azodo C et al study [15]. An oral health knowledge score was calculated by simply adding the number of correctly answered questions ranging from 0 to 7.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor oral health is related to decreased functional ability and physical fitness and decreased dietary intakes and variety (Hamalainen, Rantanen, Keskinen, & Meurman, 2004; Iwasaki et al, 2014; Iwasaki et al, 2015). Periodontitis also may cause halitosis, which can negatively impact on daily life activities such as socializing and communication with other people (Azodo, Onyeagba, & Odai, 2011). In addition, periodontitis and tooth loss causes embarrassment, negatively affecting appearance and self‐esteem (Petersen & Yamamoto, 2005; Abrahamsson, Wennstrom, & Hallberg, 2008), and can restrict social interactions.…”
Section: Discussionmentioning
confidence: 99%
“…7 Halitosis is a very common problem in dental patients; in fact most of adult subjects have socially unacceptable breath when they wake up in the morning. 8 A study performed in Japan involving 2672 individuals indicated that about 6-23% of the subjects had oral malodor as measured by Volatile Sulphur Compounds (VSC); higher than 75 parts per billion (ppb) in the expired air, at some period during the day. If these Japanese results reflect the oral malodor in other populations, then the oral malodor would represent a major oral health concern of the public.…”
Section: Introductionmentioning
confidence: 99%